A novel graphene oxide amplified fluorescence anisotropy assay with improved accuracy and sensitivity. Issue 89 (21st September 2015) - Xiao, Xue; Li, Yuan Fang; Huang, Cheng Zhi; Zhen, Shu Jun
Abstract : A novel and versatile graphene oxide (GO) amplified fluorescence anisotropy (FA) strategy with improved accuracy and sensitivity has been successfully developed. Abstract : In this contribution, a novel and versatile graphene oxide (GO) amplified fluorescence anisotropy (FA) strategy with improved accuracy and sensitivity for the detection of a panel of molecules, single-stranded DNA (ssDNA), adenosine and thrombin, has been successfully developed.